Respuesta :

-2 I think it will be that cause the 2
xy=2
x+y=-2
minus x

y=-2-x
sub
x(-2-x)=2
-2x-x^2=2
add 2x+x^2 both sides
0=x^2+2x+2
quadratic formula
if  you have
ax^2+bx+c=0
x=[tex] \frac{-b+/- \sqrt{b^{2}-4ac} }{2a} [/tex]

x^2+2x+2
a=1
b=2
c=2
x=[tex] \frac{-2+/- \sqrt{2^{2}-4(1)(2)} }{2(1)} [/tex]
x=[tex] \frac{-2+/- \sqrt{4-8} }{2} [/tex]
x=[tex] \frac{-2+/- \sqrt{-4} }{2} [/tex]
x=[tex] \frac{-2+/- \sqrt{-1}\sqrt{4} }{2} [/tex]
remember √-1=i
x=[tex] \frac{-2+/- i\sqrt{4} }{2} [/tex]
x=[tex] \frac{-2+/- 2i}{2} [/tex]
x=-1+/-i

x=i-1 or -i-1

the 2 numbers are i-1 and -i-1